Better object recognition and naming outcome with MRI‐guided stereotactic laser amygdalohippocampotomy for temporal lobe epilepsy. (8th December 2014) - Drane, Daniel L.; Loring, David W.; Voets, Natalie L.; Price, Michele; Ojemann, Jeffrey G.; Willie, Jon T.; Saindane, Amit M.; Phatak, Vaishali; Ivanisevic, Mirjana; Millis, Scott; Helmers, Sandra L.; Miller, John W.; et al.
Summary Objectives Patients with temporal lobe epilepsy (TLE) experience significant deficits in category‐related object recognition and naming following standard surgical approaches. These deficits may result from a decoupling of core processing modules (e.g., language, visual processing, and semantic memory), due to "collateral damage" to temporal regions outside the hippocampus following open surgical approaches. We predicted that stereotactic laser amygdalohippocampotomy (SLAH) would minimize such deficits because it preserves white matter pathways and neocortical regions that are critical for these cognitive processes. Methods Tests of naming and recognition of common nouns (Boston Naming Test) and famous persons were compared with nonparametric analyses using exact tests between a group of 19 patients with medically intractable mesial TLE undergoing SLAH (10 dominant, 9 nondominant), and a comparable series of TLE patients undergoing standard surgical approaches (n = 39) using a prospective, nonrandomized, nonblinded, parallel‐group design. Results Performance declines were significantly greater for the patients with dominant TLE who were undergoing open resection versus SLAH for naming famous faces and common nouns (F = 24.3, p < 0.0001, η2 = 0.57, and F = 11.2, p < 0.001, η2 = 0.39, respectively), and for the patients with nondominant TLE undergoing open resection versus SLAH for recognizing famous faces (F = 3.9, p < 0.02, η2 = 0.19). When examined on an individual subject basis, no SLAH patients experienced any performance declines on these measures. In contrast, 32 of the 39 patients undergoing standard surgical approaches declined on one or more measures for both object types (p < 0.001, Fisher's exact test). Twenty‐one of 22 left (dominant) TLE patients declined on one or both naming tasks after open resection, while 11 of 17 right (nondominant) TLE patients declined on face recognition. Significance Preliminary results suggest (1) naming and recognition functions can be spared in TLE patients undergoing SLAH, and (2) the hippocampus does not appear to be an essential component of neural networks underlying name retrieval or recognition of common objects or famous faces.